Pengaruh Value Co-Creation Terhadap Loyalitas Pelanggan Gojek di Kecamatan Medan Selayang Kota Medan - Nur Eliza, Sophia; Ayman Ashari, Muhammad; Narwastu Sianturi, Isabel; Katarina Sitanggang, Lidia; Br Bangun, Virgin Threisia; Mulyati Siregar, Afrila; Marakali Siregar, Onan (PT. Alahyan Publisher Sukabumi, 2024)
Companies in today's digital era must adapt to changing customer behavior and increase customer loyalty to maintain company values amid fierce competition. Value co-creation as a marketing strategy can be used to create company value through customer participation. This study aims to analyze the influence of value co-creation on Gojek customer loyalty in Medan Selayang District, Medan City. The method of this study is to use a quantitative method with the application of SPSS with several simple regression analysis techniques with two independent variables and dependent variables. Data collection was carried out to 100 respondents who are Gojek users in Medan Selayang District, Medan City who have used Gojek services at least 3 times. The results showed a coefficient of determination (R Square) of 0.623. This means that the value co-creation variable can explain 62.3% of the variability of customer loyalty, while the remaining 37.7% is explained by other variables that are not discussed in this study. In addition, it is known that the calculated t-value is 12,730 and the significance value is 0.000, which is less than 0.05. Therefore, the null hypothesis (H0) was rejected, while the alternative hypothesis (H1) was accepted. Overall, this study shows that the value co-creation strategy is very important for Gojek to increase customer loyalty, especially in Medan Selayang District, Medan city. This strategy can be implemented by collecting and analyzing customer feedback regularly to continuously improve Gojek's customer service in Indonesia.